2015
DOI: 10.1002/2015jc011069
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of South Equatorial Current bifurcation and western boundary currents along the Madagascar coast

Abstract: The South Equatorial Current (SEC) in the southern Indian Ocean bifurcates at the east coast of Madagascar into the Northeast and Southeast Madagascar Currents (NEMC and SEMC, respectively). In observational and reanalysis data, interannual variations of the NEMC and SEMC transports are strongly correlated with those of the SEC transport, rather than those of the SEC bifurcation latitude (SBL). Their dynamical mechanisms are then examined based on the Time‐Dependent Island Rule for the first time. It is shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…ENSO predominantly impacts the Indian Ocean south of 10°S, whereas IOD is more influential north of 10°S (Rao & Behera, ). ENSO induces wind stress curl anomalies northwest of Australia, generating interannual variations in the SEMC (Yamagami & Tozuka, ). Hence, during La Niña (El Niño) events, a stronger (weaker) SEMC is observed, at a 5‐ to 15‐months lag (Palastanga et al, ; Yamagami & Tozuka, ).…”
Section: Discussionmentioning
confidence: 99%
“…ENSO predominantly impacts the Indian Ocean south of 10°S, whereas IOD is more influential north of 10°S (Rao & Behera, ). ENSO induces wind stress curl anomalies northwest of Australia, generating interannual variations in the SEMC (Yamagami & Tozuka, ). Hence, during La Niña (El Niño) events, a stronger (weaker) SEMC is observed, at a 5‐ to 15‐months lag (Palastanga et al, ; Yamagami & Tozuka, ).…”
Section: Discussionmentioning
confidence: 99%
“…Its two branches close the interior circulations of the tropical gyre in the north and the subtropical gyre in the south, respectively. Previous studies have shown that the SEC bifurcation typically occurs at 17–18°S in the upper thermocline and extends to as far south as 22–27°S at depths near 1,000 m (e.g., Chen & Wu, ; Qu & Lindstrom, ; Rodrigues et al, ; Yamagami & Tozuka, ). We focus on the SEC south of its bifurcation, which lies roughly around 20°S taking the vertical average, and define its transport as a meridional integral of westward flow between 20°S and 40°S in the upper 2,000 m at 170°W for the South Pacific, 30°W for the South Atlantic, and 60°E for the South Indian Ocean.…”
Section: Inter‐ocean Connectionmentioning
confidence: 97%
“…We set the lag as 12 months because the lag correlation between wind stress and the Natal Pulse is maximum (r=0.52) at this lag (Figure b). This time lag is reasonable for the propagation of Rossby waves and eddies from the interior region to the Natal Bight (Yamagami & Tozuka, ). Since the regression model shows a significant effect (Figure c) and reproduces the number of the Natal Pulse relatively well, the interannual variations of the Natal Pulse are linked with the ENSO via atmospheric teleconnections to the southern Indian Ocean.…”
Section: Interannual Variability Of the Natal Pulsementioning
confidence: 74%
“…Several studies have investigated the low-frequency ocean circulation and climate in the southern Indian Ocean associated with the El Niño/Southern Oscillation (ENSO) (e.g. Rao & Behera, 2005;Ridderinkhof et al, 2013;Yamagami & Tozuka, 2015;Zhuang et al, 2013), Indian Ocean Dipole (Palastanga et al, 2006), and Ningaloo Niño (Kataoka et al, 2014). Since wind stress curl variability to the south of 10°is explained by the ENSO (Rao & Behera, 2005), here we assume wind stress curl variability in the southern Indian Ocean represents ENSO variability.…”
Section: Connection Between the Wind Stress Field In The Southern Indmentioning
confidence: 99%